The impact of bid-ask spread and trading volume activity on abnormal returns during the Period before and after the announcement of fuel price increase in Indonesia in 2022 - Ricky Bryan Tampubolon; Simon Nisja Putra zai; Hani Agustin (International Journal of Applied Finance and Business Studies, 2023)
This study examines the impact of Bid-Ask Spread and Trading Volume Activity on abnormal returns in the Indonesian capital market during the period before and after the announcement of the fuel price increase in 2022. The research considers the backdrop of the COVID-19 pandemic, which significantly affected the global economy and capital markets. The findings reveal that Bid-Ask Spread has a significant effect on abnormal returns, reflecting liquidity and demand-supply imbalances in the market. A narrow Bid-Ask Spread indicates a more stable and liquid market, reducing changes in abnormal returns, while a wide spread suggests a lack of liquidity, leading to increased transaction costs and price fluctuations. On the other hand, Trading Volume Activity does not directly influence significant changes in abnormal returns during the period surrounding the fuel price increase. Other factors, such as company performance and market sentiment, may have a more dominant role in determining stock price movements. The study highlights the complexities of the capital market during challenging economic conditions and provides valuable insights for investors, policymakers, and market participants to navigate uncertainties and crises effectively. However, the research has certain limitations, and further investigations could explore additional factors influencing abnormal returns